Integral Experiments on Critical Irradiation of 237Np and 241Am Foils at Kyoto University Critical Assembly. (2nd September 2019) - Pyeon, Cheol Ho; Yamanaka, Masao; Sano, Tadafumi; Takamiya, Koichi
Abstract: At the Kyoto University Critical Assembly (KUCA), critical irradiation experiments on 237 Np and 241 Am foils are carried out in the neutron hard spectrum core. For nuclear transmutation of minor actinides, special attention is paid to determining 237 Np and 241 Am fission reaction rates and to 237 Np capture reaction rates in the KUCA hard spectrum core. In the back-to-back (BTB) fission chamber, two nuclide foils (test: 237 Np or 241 Am; reference: 235 U) are set closely to each other to measure the aforementioned fission reaction rates. Interestingly, the experimental 237 Np and 241 Am fission and capture reaction rates are attained by critical irradiation at low W reactor power for 1 h in the core and are successfully deduced through signals from the BTB fission chamber (fission) and the gamma-ray detection (capture) after the irradiation, respectively, together with MCNP calculations.